RELATIONSHIP BETWEEN INDUSTRY BEST PRACTICES AND INFORMATION SECURITY BREACH INCIDENTS OF SACCOS IN KENYA - Sirma, Jerotich; Raburu, George; Okelo, N. B (IJRDO -Journal of Computer Science Engineering, 2015)
Information is an important organizational asset that that is mainly vulnerable to attacks from user error, hackers and crackers, viruses and cyber criminals. This has resulted in loss of trillions of dollars around the world and over 4 billion shillings in East Africa. The study investigated whether information security policies assist in preventing unauthorized individuals from accessing SACCOS’ sensitive information. The study looked at the relationship between dependent and independent variables. The study investigated the relationship between industry best practices and information security breach incidents The study used correlational survey as its research design. The study utilized a questionnaire as a survey instrument to collect responses from 85 SACCOS IT personnel with regard to their perceptions of how information security policies affect computer security breach incidents. Coefficient of variation was used to determine the sample size of 85 SACCOS registered with SASRA. Further, Simple random sampling was used to select 85 SACCOS. From the 85 SACCOS, one IT personnel was selected using simple random sampling from each SACCOS to obtain 85 IT personnel from a total of 270 IT personnel from 135 SACCOS registered with SASRA. A pilot test was carried out to test the validity of the survey instrument. Cronbach’s alpha coefficient was used to assess the internal reliability of the research instrument. Quantitative data was analyzed by using Statistical Package for Social Sciences (SPSS) version 22. Research hypotheses were tested using both 2 tailed t-tests and analysis of variance (ANOVA) tests. Pearson correlation was conducted to test the relationship between independent variables and dependent variable. Regression analysis was used to show the contribution of each independent variable to the dependent variable. Null hypothesis was tested at 95% level of confidence. If the p-value obtained is less than 0.05, then the null hypothesis was rejected, but if the p-value obtained was more than 0.05, then the null hypothesis was accepted. The results of the study revealed that there is a weak relationship between information security policies and security breach incidences in the SACCOS sector